IMPLEMENTASI PARENT-TEACHER COMMUNICATION DALAM MENINGKATKAN PRESTASI AKADEMIK SISWA (GLOBAL ISLAMIC BOARDING SCHOOL) - Elisa Putri; Aam Gunawan; Muhammad Yuliansyah (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
This study aims to describe: (1) Exploring the implementation of teacher communication at GIBS High School, including the forms of communication and platforms used. (2) Determining the impact of communication between parents and teachers on student academic achievement. (3) Identifying the inhibiting factors that affect the effectiveness of communication. This study uses a qualitative approach with a case study method. Data collection was carried out using three main techniques, namely interviews, observation, and document analysis. The data sources in this study included various stakeholders at GIBS High School, namely the principal, parents, homeroom teachers, dormitory supervisors, and students. This study clearly reveals that effective and structured teacher-parent communication is a crucial factor that is very important in supporting students' academic development, character, and discipline, and has a significant impact on students' holistic education at GIBS High School.